Cybergogy and Heutagogy Learning based on Ternate Local Wisdom for Elementary School Students’ Character Education - Sadjim, Umar M; Jusuf, Ridwan (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to assess local knowledge as one of the character formation values of Islamic elementary school students through Heutagogy and Cybergogy learning approach. The writers employed a qualitative method with a post-positivism interpretive phenomenology approach. The research subjects were the fourth, fifth, and sixth-grade teachers and students of SD (Elementary School) in Ternate. The writers collected the data through interviews, observation, and documentation and then analyzed the data using phenomenological data analysis. The results showed that the school applied Heutagogy and Cybergogy approaches in learning activities through online learning instructions combined with local wisdom. The values of local wisdom that supported the formation of student characters were tabea (respecting teachers and elders), dodara ngofa (a sense of love and affection with others), and fohaka biasa toma dodoto madaha (providing an example of habituation in education). These three dominant values formed the student characters.